Particle Attachment-Mediated and Matrix/Lattice-Guided Enamel Apatite Crystal Growth - Jokisaari, Jacob R. (ACS Nano, 2019)
Tooth enamel is a hard yet resilient biomaterial that derives its unique mechanical properties from decussating bundles of apatite crystals. To understand enamel crystal nucleation and growth at a nanoscale level and to minimize preparation artifacts, the developing mouse enamel matrix was imaged in situ using graphene liquid cells and atomic resolution scanning transmission electron and cryo-fracture electron microscopy. We report that 1–2nm diameter mineral precipitates aggregated to form larger 5nm particle assemblies within ameloblast secretory vesicles or annular organic matrix subunits. Further evidence for the fusion of 1–2nm mineral precipitates into 5nm mineral aggregates via particle attachment was provided by matrix-mediated calcium phosphate crystal growth studies. As a next step, aggregated particles organized into rows of 3–10 subunits and developed lattice suprastructures with 0.34nm gridline spacings corresponding to the (002) planes of apatite crystals. Mineral lattice suprastructures superseded closely matched organic matrix patterns, suggestive of a combination of organic/inorganic templates guiding apatite crystal growth. Upon assembly of 2–5nm subunits into crystal ribbons, lattice fringes suggesting the presence of a larger ordered crystallites were observed surrounding elongating crystal ribbons, presumably guiding the c-axis growth of composite apatite crystals. Cryofracture micrographs revealed reticular networks of organic matrix on the surface of elongating enamel crystal ribbons, suggesting that protein coats facilitate c-axis apatite crystal growth. Together, these data demonstrate (i) the involvement of particle attachment in enamel crystal nucleation, (ii) a combination of matrix and lattice-guided crystal growth, and (iii) fusion of individual crystals via a mechanism similar to Ostwald ripening.